Prefabrication of a large pedicled bone graft by engineering the germ for de novo vascularization and osteoinduction. (February 2019) - Epple, Christian; Haumer, Alexander; Ismail, Tarek; Lunger, Alexander; Scherberich, Arnaud; Schaefer, Dirk Johannes; Martin, Ivan
Abstract: Large and complex bone defects represent challenging clinical scenarios, typically requiring autologous vascularized bone transplants. In order to bypass the numerous associated limitations, here we aimed at ectopically prefabricating a bone graft surrogate with vascular pedicle. A hollow cylinder of devitalized cancellous bone was used to define the space of a large bone substitute. This space was filled with devitalized pellets of engineered hypertrophic cartilage as bone-inducing material, in combination or not with stromal vascular fraction (SVF) of adipose tissue as source of osteoprogenitors and endothelial cells. Vascularization of the space was targeted through axial insertion of an arterio-venous (AV) bundle. Constructs were subcutaneously implanted in nude rats for 12 weeks and analyzed for bone formation and vascularization by histology and microtomography. Retrieved constructs were extensively vascularized in all conditions, with vessels sprouting from the AV bundle and reaching a higher density in the axially central volume. Bone tissue was formed through remodeling of hypertrophic cartilage, and quantitatively correlated with de novo vascularization. Our study demonstrates feasibility to prefabricate large, pedicled bone grafts in predefined shapes. The combination of an AV bundle with engineered hypertrophic cartilage provided a germ for the coupled processes of vascularization and bone formation. The demonstrated osteoinductivity of devitalized hypertrophic cartilage offers the opportunity of implementing the proposed regenerative surgery strategy through off-the-shelf materials. Graphical abstract: Image 1